The Philosophy, the Art, and the Mountain (Palíndromo, 2021)
The study is a brief intellectual autobiography. It allows its author to understand how aphilosophy of art and a philosophy of existence were formed for him on objects as differentas art criticism, the music of Monteverdi, the thought of Mallarmé, the theory of therelationship between the arts in the contemporary era or the photography of the mountainlandscape and man in high mountains. This philosophy of existence in its artistic, aestheticand ethical aspects is a philosophy of freedom and perseverance based on the idea of thefragility, vulnerability and precariousness of human life, which is always being tested andconstantly reiterated. This philosophy is not fundamentally a disciplinary or academic philosophy.This philosophy cannot be exclusively conceptual since she can be constructedfrom the images of painting, of photography and literary texts.
Keywords: Aesthetics and Philosophy of Art; Alpinism and Philosophy; Intellectual autobiography; Hegel, Mallarmé